The Effect of Teachers' Role in Learning on the Learning Outcomes of High School Students - Khairil Hadi; Dazrullisa Dazrullisa; Endang Susantini; Sunu Kuntjoro (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The teacher influences the success of the learning process. Therefore, teachers need to have the ability and carry out the learning process as a learning agent as mandated by Law No. 14 of 2005. This study aims to determine the effect of the Role of the teacher as a learning agent on the learning interest of high school students. This research was conducted in SMA Negeri Aceh Barat and Nagan Rayadas, totaling 20 schools. The research sample in this study was 400 high school classes X students. Sampling was done using random sampling. The instrument used in this study consisted of a teacher questionnaire as a learning agent and a student interest questionnaire. Data analysis techniques used a simple regression test in order to determine the effect of the teacher's role as a learning agent on student learning interest. Before the simple regression test was carried out, the researcher carried out the prerequisite test, namely the data normality test and the data homogeneity test. The results showed that (1) The Role of the teacher as a learning agent was in good criteria with an average percentage of 70.8%., (2) Student interest in learning was in good criteria with an average percentage of 72.8%., and (3) The effect of the teacher's Role as a learning agent on student interest in learning is 20%.